Perancangan Tata Letak Parkiran Rumah Sakit XYZ Menggunakan Metode Craft - Vertikal Willis; Steven Steven; Anita Christine Sembiring (Jurnal Optimalisasi, 2020)
Motorcycle parking is an important facility, especially in hospitals. However, motorbike parking facilities are often neglected and tend to be built improperly, as a result, the parking facilities are poor and uncomfortable to use. This study focuses on the largest hospital in Medan. Motorcycle parking at this hospital is used as parking for PT.ABC employees and hospital visitors. This hospital parking lot is located in the basement and consists of only one narrow lane used for entrance and came out simultaneously. The impact of this parking lane is to cause long queues, especially during busy hours such as office hours. The second problem is, the parking lot is quite far from the entrance to the PT.ABC office and the entrance to the hospital so that it makes users walk further from the parking lot to their destination. The results of this study were to redesign the Layout of the motorcycle parking lot by applying the parking guidelines of the directorate general of land transportation and using the Craft method to increase the efficiency of the user's distance.